Smart Clothes as a Tangible User Interface to Affect Human Emotions using Haptic Actuators - Arafsha, Faisal (Université d'Ottawa / University of Ottawa, 2012)
Affective haptic research is a rapidly growing field. Today, more smart haptic clothes are being studied and implemented which are aimed to effect its users emotionally. However, they have some limitations. This research intends to improve the existing literature and contribute by involving consumers directly in the design of a smart haptic jacket by adding heat, vibration actuators, and by enhancing portability. In this thesis, we are interested in six basic emotions: love, joy, surprise, anger, sadness, and fear. An online survey was designed and conducted on 92 respondents that gave feedback of what it is expected from an affective haptic jacket. The results of this survey assisted in the general design, and the feedback helped to build a prototype. 86% of the respondents expressed interest in the system and are willing to try it when it is ready. A detailed design architecture is provided along with details on the hardware and software used for the implementation. Finally, the prototype was evaluated on 14 participants using the actual prototype haptic jacket based on a QoE comparison between the absence and the presence of haptic actuation. The proposed system showed improvement over a similar system that is designed for the same purpose.
Keywords: Smart Clothes; Haptic Feedback; Haptics; Jacket; Emotions; Multimedia